A mathematical model provides new insights into solid organ transplant‐associated acute graft‐versus‐host disease. Issue 9 (28th July 2016) - Rashidi, Armin
Abstract: Solid organ transplantation‐associated acute graft‐versus‐host disease (SOT‐aGvHD) is a rare but highly fatal condition. Our poor understanding of this entity in addition to its rarity has hampered treatment progress and most patients succumb to the disease. A mechanistic mathematical model is developed to replicate and explain the complex pathogenesis of SOT‐aGvHD. The model captures a number of important features of SOT‐aGvHD including (i) the occurrence of stable and persistent mixed chimerism in some, but not all, cases, (ii) fluctuation in chimerism in some persistently mixed chimeric cases, (iii) rare occurrence of full donor chimerism, and (iv) beneficial effect of escalating immunosuppression in some cases of SOT‐aGvHD and detrimental effect in others. In addition, the model predicts the conditions under which escalation or de‐escalation of immunosuppression would be the preferred treatment strategy. In an exceedingly rare condition such as SOT‐aGvHD, where prospective trials are not feasible, mathematical modeling can provide useful insights into pathogenesis and treatment.